Motif Dan Makna Joki Tugas Di Universitas Singaperbangsa Karawang - Manurung, Ayu Oktaviani; Yusup, Eka; Susanto, Tri (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
The phenomenon of task jockey services in the academic world is one form of integrity violation that is rampant among students. Although widely studied from an ethical and legal perspective, studies that reveal the motives of task jockey perpetrators are still limited. This study aims to understand the motives and meanings of students in carrying out the practice of task jockey services in the student environment of Singaperbangsa University, Karawang. A phenomenological approach is used to explore the subjective experiences of the perpetrators, through in-depth interviews with informants who have acted as task jockeys. The results of the study show that the motives of the jockeys vary, both from internal and external factors. The motives of the jockeys start from financial needs, requests for relationships, helping friends, and to hone academic skills. Meanwhile, students interpret task jockeys in various ways, starting with jockeys being interpreted as a form of self-development, helpers and also a comfortable job. These findings provide insight into the dynamics behind the practice of task jockeys and can be used as consideration for educational institutions in formulating more effective prevention policies.